(untitled) (MAUSAM, 2025)
Climate change, though inevitable, requires localized understanding of its variability to enable effective adaptation strategies, particularly in vulnerable sectors such as agriculture. This study focuses on the North Western Himalayan (NWH) region of India, encompassing Jammu & Kashmir, Ladakh, Himachal Pradesh, and Uttarakhand-areas that have witnessed substantial climatic shifts, including a 1.6 °C temperature rise over the last century and increased frequency of extreme rainfall events. Using global datasets from the GPCC and the Precipitation Concentration Index (PCI) as a key analytical tool, this research investigates spatio-temporal rainfall variability from 1971 to 2020 across varying altitudes and climate zones of the NWH region. Findings indicate a strong irregularity in precipitation distribution, particularly in J&K and Ladakh, aligning with recorded extreme rainfall events (EREs) such as 1998 J&K cloudbursts and the 2013 Kedarnath floods. The PCI values calculated for these events (e.g., 19.10 for Kedarnath) underscore the role of rainfall irregularity in disaster occurrence. Despite the observed trends, ground-based data gaps and limited infrastructure, particularly in remote or geopolitically sensitive areas, hamper precise monitoring and disaster preparedness. This study emphasizes the urgent need for enhanced climate data collection, improved documentation of EREs, and the development of microclimate-specific adaptation strategies for effective climate resilience in the North Western Himalayan region.